An estimate of the potential number of mayfly species (Ephemeroptera, Insecta) still to be described in Brazil - Cardoso,Mylena Neves (2015)
ABSTRACTThis study reviewed the data on the Brazilian Ephemeroptera, based on the studies published before July, 2013, estimated the number of species still to be described, and identified which regions of the country have been the subject of least research. More than half the species are known from the description of only one developmental stage, with imagoes being described more frequently than nymphs. The Brazilian Northeast is the region with the weakest database. Body size affected description rates, with a strong tendency for the larger species to be described first. The estimated number of unknown Brazilian species was accentuated by the fact that so few species have been described so far. The steep slope of the asymptote and the considerable confidence interval of the estimate reinforce the conclusion that a large number of species are still to be described. This emphasizes the need for investments in the training of specialists in systematics and ecology for all regions of Brazil to correct these deficiencies, given the role of published papers as a primary source of information, and the fundamental importance of taxonomic knowledge for the development of effective measures for the conservation of ephemeropteran and the aquatic ecosystems they depend on.